2016
DOI: 10.11114/jets.v5i1.2070
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Of Problematic Internet Use By Attachment In University Students

Abstract: Aim of this research is to examine the predictive power of attachment style on problematic internet use among university students. Participants of study consist of 481 university students (230 girls). Results indicate that there is a negative correlation between secure attachment style and social benefit/social comfort and there is a positive correlation between preoccupied attachment style and social benefit/social comfort which is a sub-dimension of problematic internet use. Considering predictive power of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Furthermore, it is assumed that a strong attachment bond with parents is associated with less need to use the internet for escape (Soh et al, 2014; Yang et al, 2016). Moreover, several studies have shown that attachment styles may be considered as a protective factor (Eichenberg et al, 2017; Mazaheri Nejadfard & Hosseinsabet, 2017; Kozan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is assumed that a strong attachment bond with parents is associated with less need to use the internet for escape (Soh et al, 2014; Yang et al, 2016). Moreover, several studies have shown that attachment styles may be considered as a protective factor (Eichenberg et al, 2017; Mazaheri Nejadfard & Hosseinsabet, 2017; Kozan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It includes the inclinations that arise from these networks to do thing for each other (cooperation, trust, and reciprocity) Contrary to these results, Monacis et al (2017a) found that avoidant attachment significantly predicted social media addiction, and Savcı and Aysan (2016) showed that it also predicted Internet addiction. Problematic internet use has been correlated with both being anxious (Assunção et al 2017;Mazaheri Nejadfard and Hosseinsabet 2017;Reiner et al 2017;Savcı and Aysan 2016;Shin et al 2011) and having avoidant attachment (Kozan et al 2016;Odacı and Çıkrıkçı 2014;Shin et al 2011). Blackwell et al (2017) reported that both anxious and avoidant attachment were correlated with social media addiction, and that was before they included Bfear of missing out^ (FOMO;Przybylski et al 2013) in their model.…”
Section: The Role Of the Attachment Theory In The Most Used Scalesmentioning
confidence: 99%
“…This is in line with the negative association found between secure attachment, Facebook time, and Facebook addiction (Bashir et al 2017;Eroglu 2015;Rao and Madan 2012). Moreover, it has been assumed that stronger parental attachment is related to lesser need to use the internet (Yang et al 2016) for the purpose to escape (Soh et al 2014), and studies have concluded that it may be considered a protector factor (Eichenberg et al 2017;Savcı and Aysan 2016;Mazaheri Nejadfard and Hosseinsabet 2017;Kozan et al 2016). Children's security in their relationship with parents is central to their Internet use (Assunção et al 2017).…”
Section: The Influences On Internet Engagement and Its Most Used Assementioning
confidence: 99%
“…En esta línea, algunas investigaciones han asociado el uso problemático de Internet con estilos de apego inseguros, ya sea a un estilo de apego temeroso o evitativo (Menif, Medini, Derouiche y Melki, 2016), o bien a un estilo preocupado (Kozan, Kesici, Buyukbayraktar y Yalcin, 2016), como se describirá más adelante.…”
Section: Antecedentesunclassified